(Np)QÆD HMARNIM NEBOM (B:s)E (NW)QÆR[Æ (B/s)E - (NgR)QÆN^ENKO(B, (NbORIS dMITROWI^(B,s)E 1863-1910 ((NlXW)QÆW (B:s)E (NnAKLADOM NAUKOWOGO tOWARISTWA )QÆMENI {EW^ENKA(B,s)E, 1893)
(NpRIVITT)QÃWE WIDANNQ bORISA gRÆN^ENKA(B, (NWIDANE (B"(NnAUKOWIM tOWARISTWOM ÆMENÆ {EW^ENKA(B" (NU lXWOWÆ PÆD PSEWDONÆMOM wASILQ ~AJ^ENKA(B, (NU (B1893 (NROCÆ(B, (NZ WSTUPOM AWTORA(B.s)E
"(Nz DRUKOWANIH TA NEDRUKOWANIH SWO)QÇH WÆR[ÆW Q WZQW DO CÇÃÇ KNIVKI TE(B, (N]O ZDALOSQ MENÇ KRA]IM(B. (Nq PEREGLQNUW POTÆM RUKOPIS(B. (NnEWESELA KNIVKA(B: (NVURBA TA SUM TA ^ASOM PORIWANNQ BOROTISQ ZA QSNÇ]U DOL@(B, - (NLEDWÆ BLISNE INODÇ ]OSX WESELÇ[E(B. (NnE POWESELITX TAKA KNIVKA(B, (NHIBA ZASMUTITX ^ITA^A(B! (NtA NE WKRAJ WINEN ZA CE Æ AWTOR(B! (NcE PÆWDENNE NA[E NEBO(B, (N]O POWINNO BULO(B-(NB SQTI VIWU]IM SQÃWOM(B, - (NDUVE WONO WVE NAHMARENE(B. (Na PÆD HMARNIM NEBOM NE ZASXPÆWAÃ[ WESELOÇ PÆSNÇ(B... (NkOLISX ZASXMÆÃTXCQ NA[E NEBO WESELIM PROMÆNNQM (B- (NHO^(B, (NMOVE(B, (NJ NE DO NAS UVE(B. (NtODÇ IN[Æ J SXPÆWI PO^U@TXCQ(B. (Na POKI (B- (NSXPÆWA@TXCQ TAKÆ(B, (NQKÆ MOVUTX BUTI PÆD HMARNIM NEBOM(B..." 1893 VIII 26. (IX. 7.)s)E
(NbAVANNQ (B23-25; (NbEATRI^E ~EN^I (B141-158; (Nb)QÆLA BRANKA (B52-55; (NbLAGANNQ (B168; (NbLISKU^Æ ZORÆ(B, (NNEBESNÆ SXWÆTILA (B194; (NbUWAÃ (B11; (NbURLAKA (B10-11; (NwAGANNQ (B167-168; (NwELIKA WE^ERQ (B76-77; (NwESÇLLQ (B19; (NwESNA (B162; (NwESNQNÆ SONETI (BI-XIV 119; (NwE^ÆR (B23; (NwÆDMOWI TI W MENE [UKALA (B166; (NwÆTER WIÃ(B, (NPLE]E HWILQ (B84; (NwÆTER PÆSN@(B, (NPOWNU SMUTKU (B30; (Nw NO^Æ NA MOGILÇ (B31; (NwONA SXPÆWA(B! 82; (NwOROGAM (B57-60; (NgALÇMA (B158-161; (NgORE WAM(B! 63; (NgROZA (B130-131; (NdAWNQ KAZKA (B79; (NdE WONO(B? 18; (NdOKI(B? 6; (NdOMOWINA (B5; (NdO NARODU (B34; (NdO PRACÇ(B! 7; (NdO^KA (B87-95; (NdRUZQM (B135; (NdUB (B25; (NdUH Æ TÇLO (B129; (NdU[A GORITX (B75; (NzAKLIK (B114; (NzAKOHANIJ (B82; (NzÇMA (B131; (Nz MINULOGO (B133; (NzORÆ (B95; (NzRADA (B15; (NzRADNIK (B39; æ(NWAN pOPOWI^ (B71; æ (NZGADALISX MÆNÇ NA ^UVINÇ (B80; æ (NMOLILA SQ Q (B6; (NkARA (B74; (NkOLISX BULO(B, (NWIHODILO (B26; (NkOHANNQ (B112; (NkUPANNQ (B66; (NlAWRÆN kOSTER (B136; (NmATI (B38; (NmI Z NE@ W^ORA POSWARILISX (B80; (NmINULE (B8; (NmOGILA (B13; (NmOÃ ]ASTQ (B78; (NmOLODÆ SLXOZI (B56; (NnAD dNÇPROM (B65; (NnADÇÇ (B119; (NnA DOBRA NÆ^ (B187; (NnAJBÆL[E GORE (B167; (NnA POLÇ (B14; (NnA ^UVINÇ (B30; (NnA[A DOLQ (B9; (NnEBO (B50; (NnE GORDUJ TI (B27; (NnE NA TE MI BOROTISX STAWALI (B132; (NnENA^E (B5; (NnE SUMUJTE(B! 161-162; (NnE TE MENE MU^ITX (B131; (NnÇ(B, (NNE PLA^ TI(B! 32; (NnÆ^ (B191; (NnÆ^ NA OZERÆ (B21; (Nn(B. (Nn(B. I-VIII. 60; (NnUDXGA (B55; (NoSTANNÇJ BORECX (B49; (NoSTANNÆ KWÆTKI (B77; (NoSTANNÇJ PROMÆNX (B57; (NoTAMAN mUZIKA (B68-70; (NpERED SONCEM (B192; (NpÆWDENX NA STEPU (B50; (NpÆD GNÇTOM (B26; (NpÆD NEBOM SONQ[NIM (B46; (NpIJ KUBOK VITTQ (B83; (NpO WESNÇ (B28; (NpO WESNÇ ROZCXWÆTA@TX CQ KWÆTI (B188-189; (NpODIWISX(B! 51; (NpRIJDE(B! 190; (NpRIJDUTX ^ASI(B, (NQK Æ NA[Æ (B77; (NpRO KOHANNQ PÆSNÇ (B118; (NpROMÆNNQM USE ZOLOTILO (B189; (NpROFESOR p[IK (B84; (NrANOK (B12; (NrOZMOWA (B126; (NsERED STEPÆW (B64; (NsÇM(B'(NQ (B187; (NsMERTX (B169; (NsMERTX OTAMANOWA (B105-108; (NsMUTNÆ KARTINI (B17; (NsON (B64; (NsON (BI.-V. 115; (NsONCE (B95-97; (Ns PÆSENX PRO RÆDNIJ KRAJ (B1-2. 163; (Ns ^UVINI (B65; (NtEPER(B! 39; (NtÆLKI ODNA NE PI[ALASX (B51; (NtÆLKI RAZ WSXOGO J ZUSTRÆW (B24; (NtI KAVE[(B: (NZASXPÆWAJ (B170; (NtROQNDA (B163; (NtQVKOÇ PRACÇ ZAZNAÃM (B192; (NuDOWÆ (B13; (NuKRAÇNA (B20; (Nu LÇSÇ (B37; (Nu TEMRQWÆ (B22; (NhWORA (B47; (NhLÇBOROB (B33; (NhLOPQTÇ (B19; (NhOMA mAKOGÆN (B171; (NhRISTQ (B97; (N{MATOK HLÇBA (B12; (NqK bOGOWÆ WÆR@ TOBÆ (B28; (Nq MU^IW SQ DOWGO (B81; (NqRINA (B108-112; (Nq ^U@(B, (NNENA^E (B75; (NwELIKIJ DENX (B((NmELXNICXKIJ(B) 206; (NgEJNRIH (B((NgAJNE(B) 204; (NgÆRKA DOLQ (B((NkOLXCOW(B) 201-202; (NdESPO (B((NmAJKOW(B) 199-200; (NkOHAW ODIN HLOPECX (B((NgAJNE(B) 205; (NlÇSOWIJ CAR (B(à(NETE(B) 198-199; Mag da draussen ((NgAJNE(B) 198; (NmANDRUJ(B! ((NgAJNE(B) 203; (NnASLÇDUWANNQ ANTI^NIH FORM (B(à(NETE(B) 202-203; (NnÆ^ (B((NpLE]EÃW(B) 206-207; (NpER[IJ KOWALX (B((Nz MOSKOWSXKOÇ(B) 207-209; (NpÆSNÇ OTRUTNÆ MOÇ (B((NgAJNE(B) 204-205; (NpRO P[ENIC@ (B((NbOROWIKOWSXKIJ(B) 211-212; (NsELQNINOWÆ DUMKI (B((NkOLXCOW(B) 197-198; (NsONCE TA MÆSQCX (B((NpOLONSXKIJ(B) 210-211; (Ns SLÇZ MOÇH (B((NgAJNE(B) 205-206; (NqK ZEML@ DÇLENO (B((N{ÆLLER(B) 200-201;s)E
(NnA OBKLADINC)QÆ WKAZANA WARTÆSX(B: (NcÇNA (B1 (NZR(B. (NAW(B.s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NuKRA)QÇNSXKA LÆTERATURAs)E -- (NpOEZ)QÆQs)E -- (NtEKSTIs; (NR)QÆDKÆSNE WIDANNQs)E; (NHUDODN)QÆ TWORIs)E; (NPRIVITT)QÃWÆ WIDANNQs)E